An inguinal surprise: strangulated femoral hernia - Saad, Syed; Ahmed, Mansoor; Iddalagi, Milind H. (International Surgery Journal, 2024)
Femoral hernias account for 2% to 4% of groin hernias, are more common in women, and are more appropriate to present with strangulation and require emergency surgery. This condition may lead to symptoms of bowel obstruction or strangulation and possible bowel resection-anastomosis. There are few reports of strangulated femoral hernia. Femoral hernias, often, are usually delegated to a secondary differential or if even rarer not considered at all during dubious presentations as groin swellings which are irreducible without the classical features which have usually been described in our surgical literatures, Inguinal being forefront for diagnosis. We herein present a 45-year-old female had come to the outpatient department at MVJ MC and RH with the complaints of swelling in the left groin for 5 years and pain for 8 days sudden onset with irreducibility, with no features of small bowel obstruction. She was diagnosed as having a left side obstructed inguinal hernia after appropriate radiological investigations and underwent inguinal exploration. Intraoperative diagnosis of left sided strangulated femoral hernia with omentum as its content was made. Omentectomy with herniorrhaphy was done and post-operative period was uneventful, and patient was discharged with regular follow up. Femoral hernias are more common in women and lead to a substantial over risk for an emergency operation, and consequently, a higher rate of bowel resection and mortality. Femoral hernias should be operated with high priority to avoid incarceration and be repaired with a mesh.